2018
DOI: 10.3389/ffgc.2018.00006
|View full text |Cite
|
Sign up to set email alerts
|

Grass Species Flammability, Not Biomass, Drives Changes in Fire Behavior at Tropical Forest-Savanna Transitions

Abstract: Forest-savanna mosaics are maintained by fire-mediated positive feedbacks; whereby forest is fire suppressive and savanna is fire promoting. Forest-savanna transitions therefore represent the interface of opposing fire regimes. Within the transition there is a threshold point at which tree canopy cover becomes sufficiently dense to shade out grasses and thus suppress fire. Prior to reaching this threshold, changes in fire behavior may already be occurring within the savanna. Such changes are neither empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 47 publications
5
57
2
Order By: Relevance
“…Recurrent fires maintain and structure many terrestrial ecosystems, including prairies, chaparral, savannas, and some coniferous forests. In many of these 'pyrogenic' systems, dominance of flammable grasses in the ground layer promotes the spread of fire (Beckage et al, 2011;Staver et al, 2011;Cardoso et al, 2018), which prevents ecosystem transition to a different state (Beckage et al, 2009;Callaham et al, 2012;Dantas et al, 2016;Pausas & Bond, 2019). Unlike high-profile, destructive wildfires (Chen, 2006;Hood et al, 2018), frequent low-intensity fires are essential for maintaining biotic and abiotic components of 'pyrogenic' biomes (Fill et al, 2015;He & Lamont, 2018) that include some of the most diverse plant communities on Earth (Bond et al, 2005;Noss et al, 2015;Peet et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent fires maintain and structure many terrestrial ecosystems, including prairies, chaparral, savannas, and some coniferous forests. In many of these 'pyrogenic' systems, dominance of flammable grasses in the ground layer promotes the spread of fire (Beckage et al, 2011;Staver et al, 2011;Cardoso et al, 2018), which prevents ecosystem transition to a different state (Beckage et al, 2009;Callaham et al, 2012;Dantas et al, 2016;Pausas & Bond, 2019). Unlike high-profile, destructive wildfires (Chen, 2006;Hood et al, 2018), frequent low-intensity fires are essential for maintaining biotic and abiotic components of 'pyrogenic' biomes (Fill et al, 2015;He & Lamont, 2018) that include some of the most diverse plant communities on Earth (Bond et al, 2005;Noss et al, 2015;Peet et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tree and shrub encroachment has occurred in the Great Plains grasslands and South America, Africa, Europe, Australia, and Asia (e.g., Eldridge et al, 2012). In tropical zones of the Afrotropics, Neotropics, and Australia, in regions with moderate precipitation, researchers are examining alternative ecosystem states of savannas and closed canopy forests (e.g., Cardoso et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because alternative ecosystem states and species can occur within the same climate range, or even outside of climate boundaries (Svenning and Skov, 2004;Cardoso et al, 2018), climate alone poorly predicts the global distribution of species and ecosystems (Bond et al, 2005). Additionally, annual precipitation both above and below the long-term mean occurred during the past century and millennia (Herweijer et al, 2007).…”
Section: Contradictory Evidencementioning
confidence: 99%
“…As a result, the risk of reaching a critical canopy cover threshold beyond which highly flammable shade-intolerant grasses can establish in the forest understory is expected to increase. (Hoffmann et al 2012; Silvério et al 2013; Cardoso et al 2018). Once this threshold is crossed, both fire intensity and frequency are likely to increase abruptly, as the high cover by low bulk density grass fuels in the understory dramatically increases fuel flammability (Hoffmann et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid being arrested in a fire trap (Murphy et al 2010; Grady & Hoffman 2012; Trauernicht et al 2016), the forest must be resilient, that is, recover canopy cover quickly enough to exclude shade-intolerant flammable grasses before the next fire (Hoffmann et al 2012). Many studies in both Africa and South America have identified a Leaf Area Index (LAI) of 3 as the critical canopy cover threshold at which shade-intolerant C4 grasses are excluded from the forest understory (Hoffmann et al 2012, Dantas et al 2016, Cardoso et al 2018). How climate change and deforestation will affect post-fire grass invasion and the resilience of forests to grass-fire feedback is not currently known.…”
Section: Introductionmentioning
confidence: 99%